Practical Raspberry Pi - Horan, Brendan (Apress Imprint: Apress, 2013)
Practical Raspberry Pi takes you quickly through the hardware and software basics of the Raspberry Pi. Author Brendan Horan then gets you started on a series of fun and practical projects, including a simple temperature sensor, a media center, a real-time clock, and even a security monitoring device, all of which require minimal programming experience. Along with these projects, you'll learn all about the Raspberry Pi hardware, including how it can be so powerful and still so small and inexpensive, why it's so suitable as a video player, and how you can customize it for different tasks, including running different operating systems on it, including Android and RISC OS. The Raspberry Pi is an inexpensive but relatively powerful little computer. It was designed to get kids interested in computing and programming, but it's also a great platform for hardware hackery. The projects in this book will get you deep into the hardware to show you what the Raspberry Pi can really do.